Pengaruh Beban Kerja, Komitmen Organisasi Dan Lingkungan Kerja Terhadap Kepuasan Kerja Pegawai Di Satuan Polisi Pamong Praja Kota Binjai - Rosida Sembiring (CERED Indonesia Institute, 2021)
The purpose of this study was to determine and analyze the effect of workload on organizational commitment and work environment on job satisfaction of employees of the Civil Service Police Unit of Binjai City either partially or simultaneously. The approach used in this research is an associative approach. The population in this study were all 60 employees of the civil service police unit of Binjai City. The sample in this study used a quota sampling of 60 employees of the Civil Service Police Unit of Binjai City. Data collection techniques in this study using interview techniques, documentation study, observation, and questionnaires. The data analysis technique in this study used Multiple Liner Regression Analysis Test, Hypothesis Test (t test and F test), and the Coefficient of Determination. Data processing in this study used the SPSS (Statistic Package for the Social Sciens) software program version 24.00. The results of this study prove that partially and simultaneously workload, organizational commitment and work environment have a significant effect on job satisfaction of employees of the Civil Service Police Unit of Binjai City.